Treatment of intracerebral haemorrhage with tranexamic acid: a review of current evidence and ongoing trials - Law, Zhe Kang; Meretoja, Atte; Engelter, Stefan T.; Christensen, Hanne; Muresan, Eugenia-Maria; Glad, Solveig B.; Liu, Liping; Bath, Philip M.W.; Sprigg, Nikola (Sage, 2016)
Purpose Haematoma expansion is a devastating complication of intracerebral haemorrhage with no established treatment. Tranexamic acid had been an effective haemostatic agent in reducing post-operative and traumatic bleeding. We review current evidence examining the efficacy of tranexamic acid in improving clinical outcome after intracerebral haemorrhage. Method We searched MEDLINE, EMBASE, CENTRAL and clinical trial registers for studies using search strategies incorporating the terms “intracerebral haemorrhage”, “tranexamic acid” and “antifibrinolytic”. Authors of ongoing clinical trials were contacted for further details. Findings We screened 268 publications and retrieved 17 articles after screening. Unpublished information from three ongoing clinical trials was obtained. We found five completed studies. Of these, two randomised controlled trials comparing intravenous tranexamic acid to placebo (n=54) reported no significant difference in death or dependency. Three observational studies (n=281) suggested less haematoma growth with rapid tranexamic acid infusion. There are six ongoing randomised controlled trials (n=3089) with different clinical exclusions, imaging selection criteria (spot sign and haematoma volume), time window for recruitment and dosing of tranexamic acid. Discussion Despite their heterogeneity, the ongoing trials will provide key evidence on the effects of tranexamic acid on intracerebral haemorrhage. There are uncertainties of whether patients with negative spot sign, large haematoma, intraventricular haemorrhage, or poor Glasgow Coma Scale should be recruited. The time window for optimal effect of haemostatic therapy in intracerebral haemorrhage is yet to be established. Conclusion Tranexamic acid is a promising haemostatic agent for intracerebral haemorrhage. We await the results of the trials before definite conclusions can be drawn.